Problematika Guru Pendidikan Agama Islam dalam Mengatasi Dekadensi Moral Peserta Didik di SMA Negeri 3 Merangin - Akhirudin, Muhammad; Rivauz, Ahmad (Darul Yasin Al Sys, 2023)
This study aims to identify the challenges faced by Islamic Religious Education teachers in addressing the moral decadence among students at SMAN 3 Merangin. Rapid social and cultural changes can influence the morality of students, necessitating an active role of Islamic Religious Education teachers in confronting these challenges. This research adopts a qualitative approach with a case study method to gain an in-depth understanding of the problems encountered by teachers and the efforts made to address the moral decadence of students. Data were collected through interviews with several Islamic Religious Education teachers at SMAN 3 Merangin, as well as direct observations of the teaching and interactions within the classroom. The findings reveal several factors that pose challenges for Islamic Religious Education teachers in addressing the moral decadence among students, including the influence of the social environment, the ineffectiveness of the teaching methods used, students' lack of understanding of the relevance of Islam in their daily lives, and the involvement of parents in supporting moral education at home.